2020
DOI: 10.2147/nds.s274646
|View full text |Cite
|
Sign up to set email alerts
|

<p>Micronutrients Deficiency and Their Associations with Pregnancy Outcomes: A Review</p>

Abstract: Micronutrients are vitamins, minerals and trace elements that are used in minute doses as cofactors, antioxidants and modulators of gene transcription homeostasis. MMNs may have a role in averting or treating adverse pregnancy outcomes and maternal complications. In 2016, WHO suggested the use of iron-folic acid (IFA) rather than multiple micronutrients (MMNs) during pregnancy owing to some feared adverse outcomes like perinatal mortalities. However, this effect is debatable as such complications could be also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 124 publications
0
8
0
Order By: Relevance
“…Moreover, Cheng (2019) found that MMS significantly improves communication, fine motor and problem-solving skills, and social behaviour at 36 months. A recent review concluded that MMS might have better health benefits than IFA for the babies and the mothers, 38 which contradicts the finding in a study conducted in Bangladesh. 17 MMS uses during pregnancy requires further research before a firm recommendation can be established.…”
Section: Theme 2: Relationship Between Maternal Intake and Childhood ...mentioning
confidence: 85%
“…Moreover, Cheng (2019) found that MMS significantly improves communication, fine motor and problem-solving skills, and social behaviour at 36 months. A recent review concluded that MMS might have better health benefits than IFA for the babies and the mothers, 38 which contradicts the finding in a study conducted in Bangladesh. 17 MMS uses during pregnancy requires further research before a firm recommendation can be established.…”
Section: Theme 2: Relationship Between Maternal Intake and Childhood ...mentioning
confidence: 85%
“…Iodine is an element crucial for thyroid hormone biosynthesis in humans (Sorrenti 2 et al, 2021). I deficiency diseases are caused by unsatisfactory dietary intake (Walle et al, 2020) and associated with inadequate thyroid hormone synthesis produce negative effects on the human organism, such as reproductive failure, hearing loss, impaired growth, cretinism and numerous types of brain lesions (Wang et al, 2021). Iodization of table salt has been used to mitigate this situation; however, it is not sufficient to cover the entire daily requirement (90-250 µg) in the population (Sularz et al, 2020).…”
Section: Introduction Introduction Introduction Introductionmentioning
confidence: 99%
“…On the other hand, poor maternal diet, lacking in key nutrients, is associated with adverse perinatal outcomes such as maternal anemia, pre-eclampsia, hemorrhage, and increased risk of maternal mortality. It can also lead to stillbirth, inadequate birthweight, miscarriage, and fetal development complications [5]. Thus, it is fundamental to identify modifiable dietary risk factors related to such adverse outcomes of pregnancy.…”
Section: Introductionmentioning
confidence: 99%